Evaluasi Pembelajaran Berbicara di Kelas Tinggi - Alifia Bilqish; Alliyah Putri; Try Suci Prastiwi; Juni Sahla Nasution (Lembaga Pengembangan Kinerja Dosen, 2024)
Assessing speaking ability is a complex task, more difficult than assessing listening, reading, or writing abilities. This is because what is said when speaking is quickly forgotten, so evaluation requires sufficient time to pay attention to the speaking process, not just knowledge of the material being discussed. To carry out this evaluation, the research method generally used is a review of related literature. This research involves collecting information related to a specific topic. In order for a speaking ability evaluation to be carried out successfully, it is necessary to properly understand the basic concepts, learning processes, evaluation techniques, as well as planning and implementation procedures.